Corporate governance and the going concern evaluation of Jordanian listed companies at Amman stock exchange - Zureigat, Bilal Nayef lbrahim (2015)
This study aims to examine the relationships between the aspects of corporate governance (ownership structure, board characteristics, audit committee, and audit quality) on going concern evaluation in Jordan. The data from 2009 to 2011 was extrapolated from the companies listed under the industrial and services sector on Amman Stock Exchange, resulting in the final sample of 339 firms after the exclusion of financial sectors and firms of unnecessary data due to the lack of disclosure. Multiple regression analysis revealed a positive and significant relationship between managerial and foreign ownership, board meeting, board size, audit fees, audit firm size and non-audit services with going concern evaluation. The findings also supported the positive and non-significant relationship between audit committee and going concern evaluation. On the other hand, the study drew forth a negative relationship between institutional and family ownership, board independence, and CEO duality with going concern evaluation. Theoretically, the study suggests the application of agency theory may prove more appropriate than accountability theory in describing the practices of corporate governance in developing countries such as Jordan. From a practical perspective, the findings provide feedback to the regulators (e.g. Capital Market Authority and Policy Makers) and the companies in Amman Stock Exchange in a number of ways such as promoting good practice of corporate governance among Jordanian firms. This study finds the corporate governance mechanisms play an effective role for companies as a going concern. In addition, this study opens up avenues for more studies on quality of financial reports